EU WORK-LIFE INTEGRATION: LEGISLATIVE DEVELOPMENTS - ANDREI DALINA-MARIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2023)
The objective of this paper is to analyze the evolution of work-life balance legislation in the European Union (EU), from its adoption in 2019 to its mandatory implementation among member states in 2022 or later, prompted by EU infringement procedures. Our research begins with an overview of first steps taken towards such policies since 2017, elucidating the concepts and significance of work-life balance in contemporary society, and briefly discussing the historical context of relevant laws and acts that paved the way for the most recent one, Directive EU 2019/1158. Additionally, we will outline the key provisions of the work-life balance directive and highlight primary studies that have monitored its implementation across EU member states (such as Coface, Deloitte, European Commission, etc.). Our paper will be added to literature which contributes to a better understanding of work-life balance legislation of the European Union also by updating about its implementation in all EU 27 member states.